FIKRI ARDIANSYAH1, YUSRAN PARIS2, SUNDARI RAHMAN3 - Fikri Ardiansyah; Yusran Paris; Sundari Rahman (BJRM (Bongaya Journal of Research in Management), 2025)
This study aims to examine the effect of marketplaces and payment methods on the consumptive behavior of the people of Makassar City in purchasing fashion products. The background of this research is based on the rapid development of marketplaces and digital payment systems, which have transformed consumer consumption patterns to become more practical, faster, and increasingly impu lsive. This study employs a quantitative approach using multiple linear regression analysis on 120 respondents who are marketplace users in Makassar City. The results show that, partially, the marketplace variable has a significant effect on consumptive behavior with a t-value of 7.555 and a significance level of < 0.001. The payment method variable also has a significant partial effect on consumptive behavior with a t-value of 5.654 and a significance level of < 0.001. Meanwhile, simultaneously, both variables strongly influence consumptive behavior, with an F-value of 140.197 and a coefficient of determination (R Square) of 0.865, indicating that 86.5% of the variation in consumptive behavior can be explained by marketplace and payment method variables. These findings indicate that accessibility, interactive features in marketplaces, and the flexibility of payment methods such as e-wallets, pay later, and QRIS play an important role in driving consumptive behavior, particularly in fashion products.   Keywords: Marketplace, Payment Methods, Consumptive Behavior, Fashion Products, Makassar City